An investigation into the transnational identity of Chinese student returnees from the UK - Wang, Suyang (2018)
This study explores the meaning of transnational identity of Chinese student returnees from the UK. The study is set in the context of transnationalism in the new era of globalisation. The scientific importance of this research lies in that it seeks to understand transnational identity in student returnees'experiences under the theory of transnationalism. It fills the research gap by providing a new theoretical perspective and methodological approach to identity. Under transnationalism, the study not only explores identity changes in a particular country and culture, but investigates it in the changing and overlapping countries and cultures, especially in China and the UK.